Participation in Sports-Related Extracurricular Activities: A Strategy That Enhances School Engagement - St-Amand, Jerome; Girard, Stéphanie; Hiroux, Marie-Hélène; Smith, Jonathan (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
This article outlines a strategy that we, as high school teachers, used in the academic year 2012-2013 to improve a student’s school engagement. Extracurricular activities such as sports have proven useful (among other strategies) to counter school disengagement, specifically in enhancing positive social relations among the teachers and students involved. The authors present an approach implemented in partnership with the students, and discuss the consequences of this strategy for the students and the desired improvements. Finally, we emphasize the importance of peer involvement, teachers’ collaboration, and the teachers’ willingness to inspire and empower change.